Restauración de dientes tratados endodónticamente, selección de materiales innovadores: una revisión bibliográfica - Sánchez-Loor, Fausto Andrés; Guerrero-Naranjo, Roger Iván; Marín-Vega, Gabriela Ximena (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2026)
Endodontically treated teeth are more susceptible to fracture due to the loss of dental tissue from caries, endodontic access, and the absence of pulp sensitivity. Their successful rehabilitation depends not only on endodontic factors but also on an appropriate restoration that guarantees sealing, function, and esthetics, while preserving as much of the remaining structure as possible. This research aims to highlight the importance of selecting the appropriate restorative treatment for endodontically treated teeth, considering the degree of dental involvement, occlusal stability, and the properties of available innovative materials. A narrative review of the scientific literature published between 2015 and 2024 was conducted using databases such as PubMed, Scopus, Web of Science, SciELO, and Google Scholar. Studies on restorative materials for endodontically treated teeth were included, with an emphasis on mechanical strength, adhesion, and biocompatibility. In vitro or in vivo studies lacking robust theoretical support were excluded. The study concluded that there is no single ideal material for endodontically treated teeth. The selection should be individualized. Evidence supports minimally invasive approaches when possible, prioritizing tooth preservation, effective adhesion, and long-term functionality. More randomized clinical trials are needed to solidify these recommendations.